Brokeback Mountain - Lee, Ang, 1954-; Ledger, Heath, 1979-; Gyllenhaal, Jake, 1980-; Quaid, Randy, 1953-; Hathaway, Anne, 1982-; Williams, Michelle, 1980-; Prieto, Rodrigo; Santaolalla, Gustavo; Proulx, Annie; Focus Features; Universal Studios Home Entertainment (Firm) (Universal City, CA : Focus Features : Distributed by Universal Studios Home Entertainment, 2006)
It's 1963, a time in the United States when life was simple, straightforward and the lines between the sexes and sex roles were crisply drawn and severely delineated. Ennis Del Mar and Jack Twist find themselves thrown together when they are hired to tend sheep in the remote area of Brokeback Mountain, Wyoming. Because of the job, the two are forced to spend many hours together alone in the wild. Ennis and Jack are inexorably drawn to each other through their proximity, loneliness and through a shared lack of tenderness and emotion in their lives and are emotionally, physically and psychically bonded to each other almost from the start.
Title from container.
Based on the short story by Annie Proulx.
Originally released as a motion picture in 2005.
Director of photography, Rodrigo Prieto ; art director, Laura Ballinger ; editors, Geraldine Peroni, Dylan Tichenor ; music, Gustavo Santaolalla ; costume designer, Marit Allen ; production designer, Judy Becker.
Heath Ledger, Jake Gyllenhaal, Randy Quaid, Anne Hathaway, Michelle Williams, David Harbour, Anna Faris, Linda Cardellini, Scott Michael Campbell, Larry Reese.
MPAA rating: R; for sexuality, nudity, language and some violence.
Keywords: Ranch life -- Wyoming -- Drama; Men -- Conduct of life -- Drama; Male homosexuality -- Wyoming -- Drama; Films for the hearing impaired; Romance -- Feature; Melodrama; Feature films; Romance drama